Europe’s Seminal Proto-Fascist? Historically Approaching Ziya Gökalp, Mentor of Turkish Nationalism - Kieser, Hans-Lukas (Die Welt des Islams, 2021)
Abstract This essay considers Ziya Gökalp, the received “spiritual father of Turkish nationalism”, as an early mastermind of fascism in Greater Europe. During the 1910s, Gökalp acted as a prophet of expansive war and as a mentor of demographic engineering in the Ottoman capital, Istanbul, which was a laboratory for new political styles in a crisis-ridden empire. Gökalp’s thinking longed for a supreme leader in an army-like, disciplined and hierarchised society, while it rejected a social contract-based nation and state. An influential inspiration for and beyond the new élites in the capital, Gökalp combined the call for radical modernisation according to “European civilisation” with an assertive essentialism based on völkisch (cultural-racial-ethnic Turkish) and religious (political Islamic) references. He was the chief ideologist of the Young Turk party-state (1913–18) – side by side with Talaat Pasha, its main executive leader – and “the father of my thoughts” for Kemal Atatürk.